Investigation of annular/central collapse events triggered by the double tearing modes in EAST. (2nd September 2021) - Xu, Ming; Hu, Liqun; Zhou, Tianfu; Zhang, Ling; Xu, Liqing; Duan, Yanmin; Zang, Qing; Liu, Haiqing; Gong, Xianzu; Xu, Guosheng; EAST Team, the
Abstract: Annular/central collapses of electron temperature have been investigated in the EAST tokamak. The precursor modes are excited before the annular/central collapse events, and the coexistence of multi magnetic island chains can be observed synchronously for the core concentration of high- Z impurities. The primary magnetic islands for the two cases are located in the same region of 0.25 ⩽ ρ ( r / a ) ⩽ 0.35, while the secondary magnetic islands for central and annular cases are located inside ( ρ ≈ 0.1) and outside ( ρ ≈ 0.4) respectively. The similar simulation has been performed by the toroidal resistive MHD code CLT (Zhang et al 2020 Phys. Plasmas 27 122509), and the annular/central collapse events can be reproduced by the magnetic reconnection of m / n = 2/1 double tearing modes, m and n are the poloidal and toroidal mode numbers respectively. The combination of lower hybrid current driven and off-axis electron cyclotron resonance heating is an essential condition for the establishment of reversed magnetic shear. The different penetration depth of high- Z impurity density plays an important role for excitation of the annular/central collapse events, e.g. the steeper gradient of T e -profile can be formed accordingly in the annular region of 0.1 ⩽ ρ ⩽ 0.4, together with excitation of the precursor modes.